2017
DOI: 10.1039/c7ra08150b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of electrolyzed oxidizing water with a platinum electrode prepared by magnetron sputtering technique

Abstract: EO water has the maximum value of available chlorine content when prepared by the Pt-MS electrode due to its good selectivity for CER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Therefore, it can be concluded that using only Pt as an electrocatalyst for the electrode, where the oxidation-reduction (redox) reaction of chlorine takes place, is not as feasible as it seemed in the first research. Platinum is too expensive, especially considering the low electrocatalytic activity and stability it has for CER [52]. Furthermore, taking into account that the main support material is carbon, which suffers corrosion, the most viable option is to improve the structure of Pt as an electrocatalyst with the addition of other metals and thus, optimizing support materials.…”
Section: Platinum-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be concluded that using only Pt as an electrocatalyst for the electrode, where the oxidation-reduction (redox) reaction of chlorine takes place, is not as feasible as it seemed in the first research. Platinum is too expensive, especially considering the low electrocatalytic activity and stability it has for CER [52]. Furthermore, taking into account that the main support material is carbon, which suffers corrosion, the most viable option is to improve the structure of Pt as an electrocatalyst with the addition of other metals and thus, optimizing support materials.…”
Section: Platinum-based Catalystsmentioning
confidence: 99%
“…Electrocatalytic oxidation can cause a decrease in the efficiency of Pt as a catalyst due to the formation of intermediates, which occupy the active sites. For this reason, other metals are added to improve the catalytic activity of Pt [52].…”
Section: Platinum-based Catalystsmentioning
confidence: 99%
“…However, our experimental results showed that the maximum ORP level of HOCl was between pH 2 and 3. S. Wei et al reported similar results for EO water with low pH (2.2–2.7) and high ORP (>1100 mV) produced by electrolysis of a dilute NaCl solution in an electrolysis chamber with a Pt/Ti electrode [ 30 ]. The electrode material is the key parameter related to current efficiency and stability for the formation of active chlorine in EO water production [ 31 ].…”
Section: Discussionmentioning
confidence: 81%
“…Ru 46,47 and Ir 48,49 electrodes have high electrolysis efficiency but poor stability. Pt electrode has good stability, 50 but its electrolysis efficiency of conventional electroplating platinum is not high. Therefore, from the point of view of electrolysis efficiency, the effects of Pt electrodes with different thermal decomposition temperatures on AEOW's pH, ORP and ACC values were systematically investigated in this paper.…”
Section: Introductionmentioning
confidence: 99%